Impact of Terrestrial Input on Deep-Sea Benthic Archaeal Community Structure in South China Sea Sediments - Lai, Dengxun; Hedlund, Brian P.; Xie, Wei; Liu, Jingjing; Phelps, Tommy J.; Zhang, Chuanlun; Wang, Peng (Frontiers in Microbiology, 2020)
Archaea are widespread in marine sediments and play important roles in the cycling of sedimentary organic carbon. However, factors controlling the distribution of archaea in marine sediments are not well understood. Here we investigated benthic archaeal communities over glacial-interglacial cycles in the northern South China Sea and evaluated their responses to sediment organic matter sources and inter-species interactions. Archaea in sediments deposited during the interglacial period Marine Isotope Stage (MIS) 1 (Holocene) were significantly different from those in sediments deposited in MIS 2 and MIS 3 of the Last Glacial Period when terrestrial input to the South China Sea was enhanced based on analysis of the long-chain n-alkane C31. The absolute archaeal 16S rRNA gene abundance in subsurface sediments was highest in MIS 2, coincident with high sedimentation rates and high concentrations of total organic carbon. Soil Crenarchaeotic Group (SCG; Nitrososphaerales) species, the most abundant ammonia-oxidizing archaea in soils, increased dramatically during MIS 2, likely reflecting transport of terrestrial archaea during glacial periods with high sedimentation rates. Co-occurrence network analyses indicated significant association of SCG archaea with benthic deep-sea microbes such as Bathyarchaeota and Thermoprofundales in MIS 2 and MIS 3, suggesting potential interactions among these archaeal groups. Meanwhile, Thermoprofundales abundance was positively correlated with total organic carbon (TOC), along with n-alkane C31 and sedimentation rate, indicating that Thermoprofundales may be particularly important in processing of organic carbon in deep-sea sediments. Collectively, these results demonstrate that the composition of heterotrophic benthic archaea in the South China Sea may be influenced by terrestrial organic input in tune with glacial-interglacial cycles, suggesting a plausible link between global climate change and microbial population dynamics in deep-sea marine sediments.